Use of probiotic strains to produce beers by axenic or semi-separated co-culture system - Silva, L.C. (2021)
This study evaluated the production of beers to serve as matrices for probiotic delivery and designed suitable fermentation systems. Two types of beers (wheat and sour) were produced by fermentation in an axenic (Saccharomyces cerevisiae var boulardii 17) or semi-separated co-culture system (Lacticaseibacillus paracasei DTA-81 and Saccharomyces cerevisiae S-04). Firstly, trial was carried out to investigate microbial interactions between L. paracasei DTA-81 and Saccharomyces (n = 4) and to determine the best cultivation system to produce sour beer. S. boulardii17 potential to ferment the beer wort was similar to those observed for other brewer yeasts, enabling potentially probiotic wheat beer production. L. paracaseiDTA-81 was able to ferment the beer wort to produce potentially probiotic sour beer. However, the cultivation system should be carefully designed to protect the lacticaseibacilli from stressful metabolites produced during yeast fermentation, especially alcohol. Thus, data obtained herein showed that the co-culture system should be avoided for potentially probiotic sour beer production, in order to prevent competitive interaction between lacticaseibacilli and yeast. Otherwise, the semi-separated co-culture system resulted in a symbiotic commensal interaction, without interfering on L. paracasei DTA-81 growth and survivability. Therefore, wheat and sour beers can be highlighted as useful matrices to deliver probiotic strains.